2021
DOI: 10.1021/acs.inorgchem.1c00204
|View full text |Cite
|
Sign up to set email alerts
|

Crystal and Substituent Effects on Paramagnetic NMR Shifts in Transition-Metal Complexes

Abstract: Nuclear magnetic resonance (NMR) spectroscopy of paramagnetic molecules provides detailed information about their molecular and electron-spin structure. The paramagnetic NMR spectrum is a very rich source of information about the hyperfine interaction between the atomic nuclei and the unpaired electron density. The Fermi-contact contribution to ligand hyperfine NMR shifts is particularly informative about the nature of the metal–ligand bonding and the structural arrangements of the ligands coordinated to the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 58 publications
2
27
0
Order By: Relevance
“…In that study, a pronounced effect of the exchange fraction on the hyperfine coupling was found. Nowotny et al employed embedded cluster models and the PBE0 hybrid functional to calculate NMR shifts of Cr­(III) and Cu­(II) compounds . Spin–orbit effects were taken into account with the ZORA approach.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that study, a pronounced effect of the exchange fraction on the hyperfine coupling was found. Nowotny et al employed embedded cluster models and the PBE0 hybrid functional to calculate NMR shifts of Cr­(III) and Cu­(II) compounds . Spin–orbit effects were taken into account with the ZORA approach.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Nowotny et al employed embedded cluster models and the PBE0 hybrid functional to calculate NMR shifts of Cr(III) and Cu(II) compounds. 70 Spin−orbit effects were taken into account with the ZORA approach. Ott et al calculated the diamagnetic orbital shift, the Fermi-contact shift, and the pseudocontact shift of iron (II) hydrido complexes in solution with B3LYP.…”
Section: Inorganic Chemistrymentioning
confidence: 99%
“…The 1 H MAS NMR spectrum of 1-SiO2-1 in Figure 2 shows a substantial sideband manifold, consistent with large 1 H chemical shift anisotropies associated with the paramagnetic nature of surface Cr sites. [13,15,24] Besides the spinning sidebands, the 1 H ss-NMR spectrum of 1-SiO2-1 shows a weak, highly deshielded signal at 318 ppm, together with a more intense signal around 155 ppm. The latter disappears after long acquisition times (~days) regardless of the temperature of the measurement, indicating the sensitivity of the associated surface species.…”
Section: H Chemical Shifts In the Industrial-like Uc Catalystmentioning
confidence: 99%
“…Moreover, when single crystals cannot be obtained, the structure elucidation of the system becomes challenging due to the paramagnetic center, especially if solid-(ss-NMR) and solution state (ls-NMR) nuclear magnetic resonance methods are employed. [18][19][20][21][22][23] For that reason, in this work we report a simple method to obtain two water-soluble copper complexes derived from 3acetylpyridine (3-AcPy) and 4-acetylpyridine (4-AcPy). The characterization and determination of the catalytic activity of such complexes is also reported.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of most of these complexes involves the derivatization of the pyridine ring to obtain Schiff bases, semicarbazones, thiosemicarbazones, etc., which is sometimes difficult and expensive. Moreover, when single crystals cannot be obtained, the structure elucidation of the system becomes challenging due to the paramagnetic center, especially if solid‐( ss ‐NMR) and solution state ( ls ‐NMR) nuclear magnetic resonance methods are employed [18–23] …”
Section: Introductionmentioning
confidence: 99%